Factors Related to the Incidents of Travelers’ Diarrhea in International Travelers in The Jimbaran Area, Sub-District of South Kuta, Badung Regency - Widiarsani, Ni Putu Sandra; Yanti, Ni Luh Putu Eva; Devi, Ni Luh Putu Shinta (Journal of A Sustainable Global South; Vol 7 No 1 (2023): February 2023, 2023)
Travelers' diarrhea (TD) is the most frequent health problems experienced by foreign tourists visiting Bali. Several factors can affect TD incidence in tourists such as age, gender, origin of tourists, eating habits, length of stay, and hand washing behavior. This study aims to determine the factors associated with the incidence of travelers' diarrhea in foreign tourists in the Jimbaran area, South Kuta Sub-District, Badung Regency. This research is a quantitative research, a descriptive type of correlative research with a retrospective approach. Samples were taken at 4 hotels in Jimbaran using simple random sampling technique in order to obtain a sample of 374 tourists. Based on the results of the study, it was found that the majority of foreign tourists visiting the Jimbaran area were adult, female, mostly from Australia, and mostly experienced health complaints of travelers' diarrhea. Most of the 221 tourists who experienced travelers' diarrhea were caused by consuming 203 foods (91.9%) from outside the hotel. The results of the Chi-Square statistical test showed that there were significant differences in the incidence of travelers' diarrhea between the ages of children under five, children, adolescents, adults, and the elderly (p = 0.001; ? = 0.05). However, there was no significant difference in the proportion of travelers 'diarrhea between female tourists and male tourists (p = 0.069; ? = 0.05) and there was no significant difference in the proportion of travelers' diarrhea between tourists from the continents of Asia, Africa, America, Australia and Europe (p value = 0.899; ? = 0.05).   Keywords: Travelers' Diarrhea, International Travelers